Asuransi Proteksi Medis (Professional Indemnity Insurance) sebagai Pengalihan Tanggung Gugat dalam Sengketa Medis Dokter-Pasien - Prima Maharani Putri; Gregorius Yoga Panji Asmara (Kosmik Hukum, 2022)
The aims of this article is to analyze the suitability of professional indemnity insurance with applicable laws and regulations in Indonesia, especially in the field of health law and its implications for quality. health care in Indonesia. This research uses normative juridical approaches with statute approach and conceptual approach. Based on the results of the study, Law No. 40 of 2014 on Insurance is the attitude and anticipation of the government to encourage national development, especially in the development of the industry. insurance. The doctor-patient paternalistic relationship, which is now a partnership relationship, is characterized by therapeutic transactions and informed consent in every health service. This is based on the provisions of Law No. 29 of 2004 on Medical Practice and Regulation of the Ministry of Health No. 290 /MenKes/ Per / III /2008 on Approval of Medical Measures. Health services that are "inspanning verbintenis", risk the occurrence of disputes (medical) in the doctor-patient relationship. Medical protection insurance has been regulated in Chapter III of the Regulation of the Minister of Health no. 755 / MENKES / PER / IV / 2011 concerning the Implementation of medical committees in hospitals, number 12 point D which states that the Doctor has professional indemnity insurance, which guarantees the profession of persons or companies in legal responsibility to third parties in Medical disputes. The existence of Medical Protection Insurance can make doctors in carrying out their profession to provide health services, can feel comfortable, safe and calm because they are protected. of things that are not desirable, especially in the face of compensation claims from medical disputes that he faces. Keywords: medical protection insurance, medical disputes, doctor-patients